Constitutional Supremacy, Emergency Powers and Judicial Attitudes - Das, C.V. (Journal of Malaysian and Comparative Law, 2019)
The proclamation of a state of emergency and the resultant conferment of law-making power in the Executive is an established and accepted feature of the Malaysian Constitution. It is a position that has been affirmed by several court decisions. Consequently a body of case law has developed on this subject which has helped to define sharply the scope and limits of the 'emergency power' of the Executive in Malaysia when a Proclamation of Emergency is in force.